Gut microbiota changes in patients with Alzheimer’s disease spectrum based on 16S rRNA sequencing: a systematic review and meta-analysis - Li, Hui; Cui, Xiaopan; Lin, Yuxiu; Huang, Fengqiong; Tian, Ayong; Zhang, Rongwei (Frontiers in Aging Neuroscience, 2024)
Background The gut microbiota (GM) is hypothesized to play roles in Alzheimer’s disease (AD) pathogenesis. In recent years, many GM composition and abundance investigations in AD patients have been conducted; however, despite this work, some results remain controversial. Therefore, we conducted a systematic review and meta-analysis using 16S ribosomal RNA (16S rRNA) sequencing to explore GM alterations between patients with AD spectrum and healthy controls (HCs). Methods A systematic and comprehensive literature search of PubMed, Web of Science, Embase, the Cochrane Library, China National Knowledge Infrastructure, China Biology Medicine disc database, WanFang database and Social Sciences Citation Index databases was conducted from inception to January 2023. Inclusion and exclusion criteria were strictly defined, and two researchers independently screened and extracted information from selected studies. Data quality were evaluated according to the “Cochrane system evaluator manual” and pooled data were comprehensively analyzed using Stata 14 software with standardized mean differences (SMDs) and 95% confidence intervals (95% CIs) used to measure effect sizes. Also, geographical heterogeneity effects (related to cohorts) on GM abundance were examined based on subgroup meta-analyses if sufficient studies reported outcomes. Finally, publication bias was assessed using funnel plots. Results Out of 1566 articles, 13 studies involving 581 patients with AD spectrum and 445 HCs were deemed eligible and included in our analysis. In summary, a decreased microbiota alpha diversity and a significantly distinct pattern of clustering with regard to beta diversity were observed in AD spectrum patients when compared with HCs. Comparative analyses revealed a decreased Ruminococcus, Faecalibacterium, Lachnospira, Dialister, Lachnoclostridium, and Roseburia abundance in AD spectrum patients while Phascolarctobacterium, Lactobacillus, and Akkermansia muciniphila were more enriched in patients when compared to HCs. Furthermore, regional variations may have been in play for intestinal microbes such as Bacteroides, Bifidobacterium, and Alistipes. Conclusion Our meta-analysis identified alterations in GM abundance in patients with AD spectrum, with 12 genera from four major phyla significantly associated with AD. Moreover, we provided evidence for region-specific alterations in Bacteroides, Bifidobacterium, and Alistipes abundance. These findings may have profound implications for the development of innovative GM-based strategies to prevent and treat AD. Systematic review registration https://doi.org/10.37766/inplasy2024.6.0067, identifier INPLASY202460067.